Fruitful Decades for Canthin-6-ones from 1952 to 2015: Biosynthesis, Chemistry, and Biological Activities - Jiangkun Dai; Na Li; Junru Wang; Uwe Schneider (Molecules, 2016)
In this review, more than 60 natural canthin-6-one alkaloids and their structures are considered. The biosynthesis, efficient and classic synthetic approaches, and biological activities of canthin-6-one alkaloids, from 1952 to 2015, are discussed. From an analysis of their structural properties and an investigation of the literature, possible future trends for canthin-6-one alkaloids are proposed. The information reported will be helpful in future research on canthin-6-one alkaloids.